Revisiting the Harm of Hate: A Quasi-Experimental Approach Using the National Crime Victimization Survey - Holder, Eaven (Journal of interpersonal violence, 2024)
Early legal challenges to the 1990 Hate Crime Statistics Act were originally excused on the argument that hate crimes “hurt more,” but there remain some empirical gaps on this topic. Although many works have concluded that biased offenders cause greater harms to their victims relative to unbiased perpetrators, this effect tends to be sensitive to individual and situational factors like victim and offender characteristics, bias motivation, weapon use, or crime location. This type of confounding has the potential to introduce selection bias in the estimation of victimization harms among biased criminal incidents. With data from the National Crime Victimization Survey (2010–2020), I use propensity scores and inverse-probability weighting to show that, on average, victims of bias motivated offenses are more likely to report later physical and emotional harms despite not suffering greater initial injury in incidence. Findings also demonstrate that the harm of hate varies across different bias motivations, with such crimes directed toward those on the basis of disability, gender, and sexual orientation causing greater short- and long-term individual trauma and damage.